Absorption of charged particles in a Reissner-Nordström black-hole: entropy evolution from relativistic quantum geometry - Arcodía, Marcos Ramiro Alfredo (2016)
Using Relativistic Quantum Geometry we show that the entropy can decrease in very small BHs, under certain circumstances, but always increases in very massive Black-Holes.